The Fukushima Daiichi nuclear power station disaster investigating the myth and reality - Bricker, Mindy Kay; Nihon Saiken Inishiatibu. Fukushima Genpatsu Jiko Dokuritsu Kenshō Iinkai (New York Earthscan from Routledge, 2014)
"In this volume and in gripping detail, the Independent Investigation Commission on the Fukushima Daiichi Nuclear Accident, a civilian-led group, presents a thorough and powerful account of what happened within hours and days after this nuclear disaster, the second worst in history. It documents the findings of a working group of more than thirty people, including natural scientists and engineers, social scientists and researchers, business people, lawyers, and journalists, who researched this crisis involving multiple simultaneous dangers. They conducted over 300 investigative interviews to collect testimony from relevant individuals. The responsibility of this committee was to act as an external ombudsman, summarizing its conclusions in the form of an original report, published in Japanese in February 2012. This has now been substantially rewritten and revised for this English-language edition"--
"When the Nuclear Safety Commission in Japan reviewed safety-design guidelines for nuclear plants in 1990, the regulatory agency explicitly ruled out the need to consider prolonged AC power loss. In other words, nothing like the catastrophe at the Fukushima Daiichi Nuclear Power Station was possible--no tsunami of 45 feet could swamp a nuclear power station and knock out its emergency systems. No blackout could last for days. No triple meltdown could occur. Nothing like this could ever happen. Until it did--over the course of a week in March 2011. In this volume and in gripping detail, the Independent Investigation Commission on the Fukushima Daiichi Nuclear Accident, a civilian-led group, presents a thorough and powerful account of what happened within hours and days after this nuclear disaster, the second worst in history. It documents the findings of a working group of more than thirty people, including natural scientists and engineers, social scientists and researchers, business people, lawyers, and journalists, who researched this crisis involving multiple simultaneous dangers. They conducted over 300 investigative interviews to collect testimony from relevant individuals. The responsibility of this committee was to act as an external ombudsman, summarizing its conclusions in the form of an original report, published in Japanese in February 2012. This has now been substantially rewritten and revised for this English-language edition. The work reveals the truth behind the tragic saga of the multiple catastrophic accidents at the Fukushima Daiichi Nuclear Power Station.It serves as a valuable and essential historical reference, which will help to inform and guide future nuclear safety and policy in both Japan and internationally"--
A Fukushima Diary, March 11-16, 2011 -- Nuclear Energy Development in Japan -- The Safety Myth -- Actors in Japanese Nuclear Safety Governance -- International Safety -- Accident Preparedness and Operation -- Impact of Radioactive Material Released into the Environment -- Communicating the Fukushima Disaster -- US-Japan Relationship -- Lessons of the Fukushima Daiichi Nuclear Power Station Accident and the Quest for Resilience.
"Published in association with the Bulletin of Atomic Scientists and the Rebuild Japan Initiative Foundation."
Includes bibliographical references (pages 229-238) and index.
Keywords: Fukushima Nuclear Disaster, Japan, 2011.; Disaster relief -- Japan -- Fukushima-ken.; Nuclear power plants -- Accidents -- Investigation -- Japan -- Fukushima-ken.; TECHNOLOGY & ENGINEERING / Power Resources / Nuclear